Teachers’ Perception of Numeracy in Mathematics Learning in the Merdeka Curriculum - Khomaria, Isti; Jupri, Al (Universitas Pendidikan Indonesia, 2024)
The new curriculum which is the Merdeka Curriculum is designed to help students develop the numeracy skills they need to succeed in the twenty-first century. The success of elevating students’ numeracy skills depends on teachers’ perception of numeracy as it would impact their teaching method in mathematics learning. This study aimed to explore teachers’ perceptions of numeracy in mathematics learning in the Merdeka curriculum. A case study and purposive methodology sampling were employed in this qualitative research method. The subjects are six classroom teachers in one public elementary school in Kebumen Regency, Central Java. The research data were collected by interviews, observations, and documentation. It was analyzed by interactive technique done by collecting data, data reduction, data presentation, and pull conclusion. This study realized it was essential to build numeracy skills from early grades. They had a fair understanding of how important it is to prepare for the national assessment. However, they were missing a crucial point in which the focus on numeracy was to improve the quality of mathematics learning, yet teachers had a misunderstanding and did numeracy drills as a separate part of mathematics learning. Teachers were unaware of “AKM Kelas” and how helpful it could be to help them to teach at the right level. This study’s findings contributed to stakeholders to reflect and conduct intensive workshops for teachers to escalate their performance in designing learning environments that enrich students’ numeracy skills.